Perbandingan Desalinasi Air Laut Berbasis Metode Evaporasi Dengan Tenaga Panas Api Dan Matahari - Nurul Amalia Silviyanti; Helmilia Putri; Alfarish Ramadhan (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2023)
Our Earth is a blue planet, two-thirds of which is water. However, 20% of the earth's human population suffers from a lack of clean water. Desalination is the process of converting seawater into fresh water. This research aims to convert seawater into potable fresh water by evaporation using heat energy. The heat energy used is heat from burning fire and heat from sunray. These two energy sources will be compared and analyzed for their efficiency in desalinating seawater into fresh water. Heating using fire is done by burning twigs and dry leaves, and then two glass bottles are connected to the mouth of the bottle so that there is no air in or out. The collected water vapor will flow into the empty bottle. The second method uses sunray for heating. The two clear bottles are connected with a small pipe at the mouths of the bottles. Seawater is collected in the bottle and then dried under direct sunlight. The evaporated water will pass through the connecting pipe and gather in the empty bottle above. Fresh water produced from heating using fire was collected as much as ±7 ml in a span of 20 minutes, while heating using sunray can produce ±2 ml of fresh water in a span of 70 minutes or 1 hour 10 minutes.